STUDY OF IMPACT OF FRESH FRUIT BUNCH (FFB) OF PALM FRUITS ON DIFFERENT SURFACES - Yuwana, Lukman Hidayat dan Bosman Sidebang (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTPhenomena of impact of oil palm’s FFB against ground, concrete, wood, metal and FFB surfaces were studied to determine bruise resistance and minimum absorbed energy to cause bruising. Employing free fall and pendulum impact methods, results of the experiment indicated that the values of bruise resistances of FFBs impacted against ground, concrete, wood, metal and FFB surfaces were 0.1175 J/mm3, 0.0095 J/mm3, 0.0074   J/mm3, 0.0089 J/mm3 and 0.0077 J/mm3, respectively. The values of minimum absorbed energies to cause bruising of FFBs impacted against ground, concrete, wood, metal and FFB surfaces were 334.46 J, 8.9671 J, 19.401 J, 17.553 J and 9.5925 J,  respectively. In respect to fruit ripeness, the change of bruise resistance value followed an uncertain trend whereas the values of minimum absorbed energy to cause bruising decreased with the advance of fruit ripeness. In order to avoid bruising during handling due to impact against those five different surfaces, FFBs must be protected from suffering from energy greater than their minimum absorbed energies. Keywords: impact, bruise resistance, palm fruit, surfaces